(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Today, the corporeal has taken a solid place in public space. The active position of a person in relation to his body and physical perfection is concretized in different types of behavior, the body actively participates in various kinds of demonstrations, games, and competitions. For example, some people are consciously engaged in fitness, aerobics, bodybuilding, dancing, yoga, shaping, making tattoo, piercing, doing plastic surgery, visiting solarium, saunas, and massage centers for the optimal body care. The values of body formation should include health preservation and strengthening, muscle development, optimal preparation for the needs of military service, the recovery of the lost body functions, the formation of movement culture, physique. Such approaches must go hand in hand with the development of intelligence, memory, thinking, creativity, aesthetic and moral qualities. Physical education and sports training refer to those areas in which, like nowhere else, human corporeality is manifested in its cultural aspect. 80 The primary purpose of this research is to highlight the essence and content of the phenomenon of bodily culture and bodily education of human through the prism of physical education and sports training process. The article discusses and summarizes the values for the formation of human corporeality, issues of bodily culture and bodily education relying on pedagogical, philosophical, sociological literature sources. Some methods and techniques, programs and concepts of bodily culture and bodily education are highlighted.